Planejamento e controle para produção de alface hidropônica com auxílio de planilhas eletrônicas - Heintze, Taiomara Cardoso Dal'Sotto (2018)
With the need for food production to meet the contemporary demand and reduction of growing areas, there is a need for new planting techniques to meet the demand of the population. The hydroponics is a technique widely used cause it presents production throughout the year. However, the demand for vegetables has increased as well as the competition. This study proposes to perform a production planning and control (PPC), and analyzed the stock, the cost of the product, sale, purchase and production of a company in the Western region of Paraná. The criteria of production was to assess the levels of nitrate in hydroponics lettuce under different flow rates, and subsequently developed spreadsheets and production control. For the development of the PPC, some information about sales, and other inputs were required. The production process was accompanied for its understanding. There were conducted analyses of moisture content, ash, organic mass, microbiological analysis of hydroponic lettuce, conventional and organic and sensory analysis by the Hedonic Scale test. The experiment was conducted in a protected environment, a small company in the West of Parana, which has Nutrient Film Technique (NFT) in the period from 20 May to 7 July 2017, through a completely randomized design. In the analysis of nitrate, 216 samples were evaluated, and 24 samples were used for the characteristics of production. The results obtained in the analysis of nitrate content in three flows were low, 1076.89 (0.5 L.kg-1), 1783.54 (L.kg-11) and 2459.73 (L.kg 1.5- 1). The results were satisfactory for the flow rate 1.5 L.min-1, which obtained 29.73g Root fresh mass, 3, 89g Fresh stem, 147, 28 g fresh pasta sheet, 151, 18 g fresh pasta, 180, 13 g Fresh Mass Total, 1, 32 g Root dry mass, Leaf dry mass 56 g, 5, 7, 22 g Total Dry Mass, 5, 90 g dry mass, 2, 29 g Unusable Leaf Number and 2459.73-1 mg.kg of nitrate content. In microbiological assessment, these three samples of lettuce showed results within the parameters of the Brazilian legislation. The lettuce organic and hydroponic systems presented the best results in relation to texture attributes, aroma, color, appearance, and overall impression. The spreadsheets were developed with the information collected. So, has developed interfaces with text boxes and buttons. These interfaces the producer can enter their data and saves them automatically in the worksheets. The calculations of the cost, selling price, demand forecasting, prediction of harvest dates and transfer bench, were automated. Thus, it is concluded that the hydroponic lettuce showed nitrate levels below the values of European legislation, satisfactory acceptance by consumers and it is stated that lettuce produced is of good quality. It was noted that the frequency of consumption of lettuce is low. The worksheets and interfaces developed will enable the producer to analyse the enterprise in a simple and practice point of view.